Večfaktorska analiza občutljivosti območij kot podlaga za prostorsko načrtovanje v Izmirju, Turčija - Kap Yücel, Seher Demet (Urbani izziv, 2023)
Sensitivity assessment produces data to guide spatial planning by determining areas that need to be protected. Izmir, the study area of this article, is a city with rich ecological values but rapidly changing spatiality. This study determines ecologically sensitive areas of Izmir and reveals the relationship between ecologically sensitive areas and spatial planning decisions. To achieve this goal, ecologically sensitive areas are defened by the Analytical Hierarchy Process (AHP) and overlapped with planning decisions. The study evaluates ecological factors and processes using nine main parameters and twenty-one sub-parameters. Each of the parameters selected was divided into ecological sensitivity levels. The result of the analysis found 16.8% of the area to have very high sensitivity, 18.5% high sensitivity, 22.7% average sensitivity, 28.5% low sensitivity, and 13.5% very low sensitivity. A comparison of these areas with the 1:100,000 Environmental Regulation Plan decisions showed that the planning decisions are not compatible with the ecological sensitivities of the study area. As a result, the study provides an ecological sensitivity assessment model that can contribute to improving decision-making processes in urban plans.
Keywords: analiza ekološke občutljivosti; analytic hierarchy process; ecological sensitivity assessment; GIS; Izmir; postopek analitične hierarhije; prostorsko načrtovanje; spatial planning